2006
DOI: 10.1007/s11064-006-9076-0
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effect of Etomidate in the Central Nervous System of Streptozotocin-Induced Diabetic Rats

Abstract: It is well known that hyperglycaemia due to diabetes mellitus leads to oxidative stress in the central nervous system. Oxidative stress plays important role in the pathogenesis of neurodegenerative changes. In the present study we investigated the possible neuroprotective effect of etomidate against streptozotocin-induced (STZ-induced) hyperglycaemia in the rat brain and spinal cord. A total of 40 rats were used in this study. Rats were divided into four groups: sham-control, diabetic, diabetic-etomidate treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 63 publications
0
12
0
Order By: Relevance
“…One striking aspect of our study was the observed disparity between changes in the expression and the density of CB 1 Rs after STZ treatment. This suggests either a modification of protein translation, as was reported to occur in the hippocampus after traumatic brain injury (Chen et al, in press), where activation of a key rate-limiting translational pathway (the mTOR pathway) is observed; or alternatively a modification of the half-life of CB 1 Rs that might be related to oxidative stress found in the hippocampus of STZinjected rats (Ates et al, 2006). In conclusion, the elevated density of the CB 1 R protein and CB 1 R binding sites may represent a compensatory or a pathophysiological process.…”
mentioning
confidence: 69%
“…One striking aspect of our study was the observed disparity between changes in the expression and the density of CB 1 Rs after STZ treatment. This suggests either a modification of protein translation, as was reported to occur in the hippocampus after traumatic brain injury (Chen et al, in press), where activation of a key rate-limiting translational pathway (the mTOR pathway) is observed; or alternatively a modification of the half-life of CB 1 Rs that might be related to oxidative stress found in the hippocampus of STZinjected rats (Ates et al, 2006). In conclusion, the elevated density of the CB 1 R protein and CB 1 R binding sites may represent a compensatory or a pathophysiological process.…”
mentioning
confidence: 69%
“…Evidence has accumulated showing the massive generation of reactive free radicals in diabetes and the resulting increase in LPO and protein oxidation which leads to cellular disintegrity of neuron [28, 29]. Lipid peroxides and protein oxidation are the secondary products of oxidative stress causing secondary injury by further generating relatively more stable and diffusible cytotoxic agents such as malondialdehyde and 4-hydroxy-trans-2-nonenal, respectively, and magnifying oxidative stress [30].…”
Section: Discussionmentioning
confidence: 99%
“…The male ZDF rat (ZDF/Gmi, fa/fa), derived from inbreeding of hyperglycemic Zucker obese rats, is characterized by a mutation in the leptin receptor with resultant high circulating leptin levels. Diabetes mellitus is associated with cerebral alterations in both human and animal models of the disease [4][5][6][7]. Hippocampal neurons are also sensitive to the effects of diabetes [6,8] and often show damage to presynaptic and postsynaptic structures, dysregulation of calcium homeostasis, neuronal loss, dendritic atrophy in CA3 neurons, reduced expression of insulin growth factors and their receptors, and decreased neurogenesis [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%